Calcination temperature-dependent structural, optical, and photoluminescence properties of Mg-Al bimetallic oxide prepared by sol-gel auto combustion method - Thanit Tangcharoen (Journal of Magnesium and Alloys)
In this research study, magnesium-aluminum (Mg-Al) bimetallic oxide powders are synthesized via the sol-gel auto combustion method using diethanolamine (DEA) as the fuel. In order to subsequently determine the influence of calcination temperatures upon the structure, chemical bonding, morphology, optical properties, and fluorescence properties of the as-synthesized and calcined Mg-Al bimetallic oxide powders, the researcher employed X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV–visible diffuse reflectance spectroscopy (UV-DRS), and photoluminescence spectroscopy (PL), respectively. It was apparent on the basis of the XRD and FT-IR analyses that those powders undergoing calcination at temperatures of 500 °C, 700 °C, and 900 °C contained the major phase magnesium aluminate (MgAl2O4) spinel with trace magnesium oxide (MgO) and hydrotalcite (Mg6Al2(CO3)(OH)16). When the calcination temperature rose to 1100 °C, this resulted in a single phase MgAl2O4 while MgO and (Mg6Al2(CO3)(OH)16) were no longer observed. UV-DRS analysis revealed that in optimized conditions, calcination resulted in better sample absorption and reflection levels when compared to the ultraviolet, visible, and infrared spectra observed in the case of the as-synthesized sample. The bandgap energy (Eg) for calcined samples was in the range of 2.65 eV to 5.85 eV, in contrast to the value of 4.10 eV for the as-synthesized sample. Analysis of photoluminescence showed that for the as-synthesized samples and those calcined at low temperatures, visible light was emitted only in the violet, blue, and green regions with low intensity, while for samples calcined at higher temperatures, the emissions showed greater intensity and extended to the yellow and orange regions. Multiple defect centers were found in the bandgap which can explain these findings.